CARDIAC ARRHYTHMIAS AFTER TRANSCATHETER CORRECTION IN PATIENTS WITH SECONDARY ATRIAL SEPTAL DEFECT - E. K. Abdyzhaparova; E. D. Dzhishambaev (Евразийский Кардиологический Журнал, 2016)
SUMMARY In order to study the dynamics of cardiac arrhythmias in patients with secondary atrial septal defect (ASD) examined 50 patients in the age of from 3 to 68 (mean age 24,2±2,1 years) with secondary defect investigated arrhythmias changes in the nearest (till 3 months) and remote (till 1 year) the periods after transcatheter closings of arial septal defect using the amplatzer septal occluder were examined. Already in 3 day after transcatheter correction marked decrease frequent (67,8 ±29,4 till 62,5±25 in hour) group supraventricular extrasystoles, disappear episodes paroxysmal atrial fibrillation and paroxysmal supraventricular taxycardias. By 6 months the disappearance of the group and reduction of frequent supraventricular extrasystoles. In relation to ventricular arrhythmias on day 3 observations marked deerease in the number of VEs (254,1±171,2 till 32,6±3,6 in hour), the complete disappearance of VEs high grade to 12 months. Thus, after transcatheter closure of ASD in the coming secondary (3 hours) and long-term (6-12 months). Deadlines are not observed occurrence of serious cardiac arrhythmias, and available undergoing a significant improvement towards a significant reduction in the number of premature beats until their complete disappearance. This fact confirms the effectiveness and safety of this method of treatment of secondary ASD. Key words: secondary interatrial septum defect, electrocardiographia, Amplatzer occluder, supraventricular and ventricular extrasystols.